2021
DOI: 10.1016/j.lungcan.2021.06.026
|View full text |Cite
|
Sign up to set email alerts
|

YAP1 protein expression has variant prognostic significance in small cell lung cancer (SCLC) stratified by histological subtypes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Among the 14 included articles, 4 articles including 6 studies ( 14 , 15 , 23 , 28 ), and 10 articles ( 13 , 18 – 22 , 24 27 ) containing 13 studies reported the relationship between TAZ and YAP and the prognosis of patients with lung cancer, respectively. Three studies, including 350 cases, reported these associations concerning SCLC in the Chinese population ( 24 , 26 ), and the other 16 studies, including 857 cases, reported these relationships concerning NSCLC. Three studies were conducted in the Caucasian population ( 13 , 14 , 21 ), and the others were performed in the East Asian population.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 14 included articles, 4 articles including 6 studies ( 14 , 15 , 23 , 28 ), and 10 articles ( 13 , 18 – 22 , 24 27 ) containing 13 studies reported the relationship between TAZ and YAP and the prognosis of patients with lung cancer, respectively. Three studies, including 350 cases, reported these associations concerning SCLC in the Chinese population ( 24 , 26 ), and the other 16 studies, including 857 cases, reported these relationships concerning NSCLC. Three studies were conducted in the Caucasian population ( 13 , 14 , 21 ), and the others were performed in the East Asian population.…”
Section: Resultsmentioning
confidence: 99%
“…Second, co‐analysis of ASCL1/DLL3 expression using routine IHC staining provides evidence for selection of potential subgroups, which is more applicable for advanced patients (accounting for 80% SCLC patients in clinical practice) because of insufficient sample amount for further examination. Third, unlike the study by Furuta et al, 12 we enrolled pure SCLC samples for study (that is more representative of authentic SCLC features compared to combined SCLC) because both of our previous works based on clinicopathological analysis 13 and YAP1 expression 14 revealed the distinction between pure SCLC and combined SCLC, and the latter presented much more heterogenicity. Although the cell origin of combined SCLC remains unclear, SCLC components and non‐SCLC components in combined SCLC have been reported to share almost 75% common mutations and show similar genetic background, suggesting that the SCLC components and non‐SCLC components are derived from common precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of both ASCL1 and DLL3 in SCLC patient samples has been only reported in one recent study, 12 which investigated 95 surgically resected SCLC samples, including combined SCLC. However, our recently published studies revealed distinct prognostic impact factors 13 and YAP1 protein expression between pure SCLC and combined SCLC 14 . This suggests that combined SCLC and pure SCLC might be different entities and present different targetable oncogenic pathways.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Still, YAP1 has been reported as one of the key transcription factors for molecular subtypes [13] , although it is not validated in studies like Gay's [14] . Our previous study found that expression of YAP1 was significantly higher in combined SCLC than that of pure SCLC as well as an unfavorable prognostic factor for combined SCLC [15] . Genomic data indicated that LCENC could be divided into SCLC-like profile ( RB1/TP53 inactivation, MYCL amplification) and NSCLC-like profile (alteration in STK11, KEAP1, KRAS, and other RAS pathway genes) [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 92%